Port-Related Complications in Laparoscopic Surgeries: A Prospective Observational Study of the Iranian Population - Hojatolah Khoshnoudi; Majid Samsami; Mojtaba Ahmadi Zivyari; Alireza Haghbin Toutounchi; Hamed Tahmasbi; Tahmaseb Jouzdani; Seyed pedram Kouchak Hosseini; Fatemeh Parsaeian; Mohammad Aghaei; Behzad Nematihonar (Iranian Journal of Colorectal Research)
Background: Despite contradictory reports regarding complication rates associated with various laparoscopictechniques, data specific to the Iranian population remain limited. In this study, we prospectively investigatedport-related complications in laparoscopic abdominal surgeries performed on individuals from the Iranianpopulation.Methods: This study was conducted as a prospective cohort at Imam Hossein Medical Center, Tehran, Iran,from 2021 to 2024. A total of 346 patients who were candidates for abdominal surgery using the laparoscopictechnique and referred to the tertiary hospital were included in the study based on the inclusion criteria.Demographic information about the patients, including age, gender, and underlying conditions, as well as datarelated to the surgery and complications associated with the port, were examined and recorded by the surgeonsfor six months following the surgery.Results: In this study, 346 patients were examined. The mean age of the patients was 44.34±11.80 years, withages ranging from 16 to 77 years. Among the patients, 206 (59.5%) were women, and 140 (40.5%) were men. Ofthe 346 patients who underwent surgery, 129 (37.3%) had a cholecystectomy, 117 (33.8%) underwent bariatricsurgery, and 71 (20.5%) had herniorrhaphy. Port-related complications were observed in 11 patients (3.2%),with port site infections diagnosed in 10 patients (2.9%). An incisional hernia was diagnosed in one patient(0.3%). There were no port site bleeding, omental injury, or other possible port-related complications.Conclusion: In this study, port-related complications among the Iranian population have been reportedfor comparison with other populations. The low complication rate of 3.2% aligns with global standards,underscoring the safety of laparoscopic procedures in well-equipped settings.